Interregional scientific conference dedicated to the 100th anniversary of the Ingush Republic - S. A. Vishnyakova (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The article is devoted to information about the conference dedicated to the 100th anniversary of the Republic of Ingushetia.Goal. Consideration of the structure and concept of the conference dedicated to statehood; the main problems of the history and modernity of Ingushetia, analytical reports and summary reports. The cultural program of the conference, presented by an exhibition of paintings, carpets, photographs, is also considered.Materials and methods. In the course of writing the article, the following methods were used: analysis of the material presented at the conference, methods of observation, identification of the main, new; analysis and synthesis of speeches; modeling of situations proposed by speakers, descriptions.Results and discussion. The result of the generalization and analysis was a description of the problems presented at the plenary session of the conference and the main problems raised at sectional meetings, as well as acquaintance with the cultural program of the conference, its significance.Conclusion. A resolution was adopted, which will undoubtedly help to highlight the most pressing problems for improving the socio-cultural situation in the region.